The mediating effect of organisation culture on transformational leadership and turnover intention in jordanian public hospitals - Alkharabsheh O.H.; Alias R.B.; Ismail M.H.B. (Society for Alliance, Fidelity and Advancement (SAFA), 2023)
This study examines how transformational leadership associated to turnover intention among nurses who are working in Jordanian public hospitals. The mediating effect of organization culture on this association is also tested. A total of 398 questionnaires were distributed to nine public hospitals and 354 nurses returned their questionnaires. Structural equation modelling (SEM) was employed to examine the mediating effect of organization culture on the relationship between transformational leadership and turnover intention. The study finds that there is a negative relationship between transformational leadership and turnover intention. Also, organization culture partly mediates the relationship between the transformational leadership and turnover intention.